A State of Review on Biomedical Image Processing Techniques with A Focus on Deep Learning - Suresh Anand.M (AG Volumes, 2022)
In recent years, the area of medical images processing has been developed into the established one. In clinical research, the accurate segmentation of medical pictures is essential for monitoring, diagnosis and planning therapy. Segmenting medical photos by hand takes a long time and is tiresome. As a result, high-accuracy segmentation algorithms for such automated data collection are highly sought after. An algorithm's efficiency may be influenced by a variety of things. For instance, the scope of a segmentation technique's applicability, the method's repeatability, the precision of its findings, and so on. With an emphasis on the Deep Learning Techniques, this paper will provide readers an overview of the current picture segmentation techniques. The review focuses on picture segmentation using deep learning with in medical imaging field.